Sistem Informasi Manajemen Arsip Daerah Pada Dinas Perpustakaan Dan Kearsipan Tanah Laut Berbasis Web - Ehsan, Muhammad; Putri, Meliana; Agung Wibobo, Dwi (Journal Information Technology Trends (JITRENDS), 2023)
The District Library and Archives Office of Tanah Laut Regency is a local government unit responsible for assisting the government in organizing library and archives affairs. In these activities, the archives are still in the form of hard copies, which can be lost or damaged in case of fire, natural disasters, and other unforeseen events. Moreover, hardcopy archives are also subject to deterioration with age. To address these challenges, the author developed a Web-Based Regional Archive Management Information System at the District Library and Archives Office of Tanah Laut. The system was built using the incremental model and programmed in PHP (CodeIgniter Framework), HTML and CSS, while being designed using Entity Relationship Diagram and Unified Modeling Language. The system underwent black-box testing conducted by Batuah Teknologi Semesta, resulting in successful testing of the system's features and performance. The data used in the Web-Based Regional Archive Management Information System at the District Library and Archives Office of Tanah Laut consists of hardcopy archive data from each department within Tanah Laut. Therefore, the system was developed to provide various features that enable users to perform essential tasks. The main features of the system include the management of inactive, obsolete, and static archives.